Zinc (II) chloride-based deep eutectic solvents for application as electrolytes: Preparation and characterization - Bagh, F.S.G.; Shahbaz, K.; Mjalli, F.S.; Hashim, M.A.; AlNashef, I.M. (Elsevier, 2015)
Deep eutectic solvents (DESs) have gained interest due to their favorable electrochemical properties. This work introduced a new group of zinc (II) chloride based DESs and characterized their melting temperatures, viscosities, electrical conductivities, refractive indices, as well as electrical window over a wide range of temperatures. The ammonium-based deep eutectic solvents possessed lower melting temperatures, lower viscosities and higher electrical conductivities in comparison to phosphonium-based ones. The deep eutectic solvent made from choline chloride and zinc (II) chloride at a mole ratio of 1:1 possessed high conductivities, 574-4779 mu S.cm(-1), relatively low viscosities, 0.8278-0.2842 Pa.s, and wide electrochemical window, 3.74 V within the studied temperature range. The attained measurements were compared with other reported deep eutectic solvents in the literature. (C) 2015 Elsevier B.V. All rights reserved.